PENDAMPINGAN PENGUATAN MANAJEMEN USAHA TERNAK AYAM BROILER PADA KELOMPOK TERNAK DI KELURAHAN KASTELA KECAMATAN PULAU TERNATE - Kaddas, Fatmawati; Fatmawati, Mila; Wahyuni, Sri; Mahmud, Haris (STKIP Persada Khatulistiwa Sintang, 2024)
ABSTRACTBroiler chicken cultivation is a potential business and is widely carried out by the community. A group of broiler chicken breeders with the name Makmur Jaya group located in Kastela Village, Ternate City, North Maluku, was formed because of the desire to work together for one goal, namely improving the welfare of its members. However, in the course of business development by the broiler chicken farming group, there were several problems, including a lack of knowledge and skills in raising chickens; livestock management has not been managed well; partner businesses are still traditional; and still use simple equipment in raising chickens. This activity was attended by members of the Makmur Jaya broiler chicken farming group and students of the Agribusiness Study Program, Faculty of Agriculture, Khairun University. Methods for implementing activities include socialization and FGD, training and mentoring. The aim of this activity is to provide knowledge to the public regarding good feed management in household-scale broiler chicken cultivation. Participants were very enthusiastic about the discussion, especially regarding the maintenance and health management of broiler chickens as well as training in broiler chicken cultivation with direct practice when the new DOC arrived at the service location.Keywords: Broiler chickens; Management; Mentoring; Livestock businessABSTRAKBroiler chicken cultivation is a potential business and is widely carried out by the community. A group of broiler chicken breeders with the name Makmur Jaya group located in Kastela Village, Ternate City, North Maluku, was formed because of the desire to work together for one goal, namely improving the welfare of its members. However, in the course of business development by the broiler chicken farming group, there were several problems, including a lack of knowledge and skills in raising chickens; livestock management has not been managed well; partner businesses are still traditional; and still use simple equipment in raising chickens. This activity was attended by members of the Makmur Jaya broiler chicken farming group and students of the Agribusiness Study Program, Faculty of Agriculture, Khairun University. Methods for implementing activities include socialization and FGD, training and mentoring. The aim of this activity is to provide knowledge to the public regarding good feed management in household-scale broiler chicken cultivation. Participants were very enthusiastic about the discussion, especially regarding the maintenance and health management of broiler chickens as well as training in broiler chicken cultivation with direct practice when the new DOC arrived at the service location..Kata Kunci: Ayam broiler; Manajemen; Pendampingan; Usahaternak